Hubungan Pegetahuan Menyikat Gigi dengan Kebersihan Gigi dan Mulut pada Siswa Tunarungu di SLB-B YPAC Banda Aceh - Mene Nabila; Eka Sri Rahayu (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Background꞉ One of the most crucial aspects of a child's development is their dental health. Children with special needs, including those who are deaf, are particularly vulnerable to dental and oral health issues. The limitations of children with hearing disorders lead to cognitive processing disorders, which affect the child's ability to receive, store, and communicate information. Methods꞉ the population used. Data was gathered by having participants complete a checklist-based questionnaire about their knowledge about brushing their teeth. Direct examination was used to gather information on dental and oral hygiene, and the OHI-S score was visible. The dates of this investigation were May 7-8, 2024. Thirty persons participated in this study as respondents. Result꞉ that this study indicates the relationship between brushing knowledge and dental and oral hygiene. with the value (P=0.001) ἀ ≤ 0, 05. Consclusion꞉ The conclusion of this study shows that this study indicates the relationship between brushing knowledge and dental and oral hygiene.